Morpho-palynological and anatomical studies in desert cacti (Opuntia dillenii and Opuntia monacantha) using light and scanning electron microscopy - Majeed, S. (John Wiley and Sons Inc, 2022)
Opuntia is the most diverse and widely distributed drought resistant promising genus of family Cactaceae. The cladodes were utilized to quantify the chemical composition of these plants helpful in lignocellulose conversion and their application towards biofuel production. The present study was aimed to evaluate and compare the taxonomic relationship based on morphology, stem anatomy and palynology of important desert cacti including Opuntia dillenii and Opuntia monacantha. This study also evaluates the potential usefulness of morphological, anatomical and pollen traits using light and scanning electron microscopy. The obtained microcharacters of stem and flowers are considered diagnostic at the generic and specific levels. Some distinguishing morphological features observed were elliptical to obovate cladodes, 1â7 spines per areole and presence of glochidia in O.Â dillenii. Pollen and stem anatomical characters of the studied taxa are considered highly diagnostic at the generic and species levels. The epidermis has irregular and wavy cells, with straight to sinuate wall pattern and paracytic stomata. Pollen grains appear as pantoporate and prolate spheroidal having reticulate to perforate-reticulate sculpturing while exine semi-tectate to tectate. The taxonomic features studied could be valuable to elaborate and helpful in correctly identification of Opuntia species. The methods of diverse microscopic examination also providing sufficient evidence about the taxonomy of the Opuntia species. Â© 2022 Wiley Periodicals LLC.